STUDIES ON DETECTION, DIAGNOSIS AND CONTROL OF LEGIONELLA PNEUMOPHILA IN DIFFERENT WATER SAMPLES - Mansour F.A.; S.A. El-Sherbiny; N.A. El-Morsy (Arab Universities Journal of Agricultural Sciences, 2006)
A number of 192 samples (180 water & swab specimens and 12 patient sputa)were chosen from different sites of Mansoura University Hospitals for detection anddiagnosis of Legionella pneumophila. Out of the 192 samples, 148 were positive byculture method and non-specific staining technique such as gram staining andbiochemical analysis. In our trials for diagnosis of Legionella pneumophila, wefound that 107 of 148 samples were positive by slide agglutination test and 110samples were positive by direct immunoflourescence assay, while 130 samples werepositive by polymerase chain reaction (PCR) technique which proved to be the mostspecific and sensitive technique for diagnostic investigation of L. pneumophila. Theresults show that the four disinfectant procedures (chlorine, ozone, U.V. light andheat) were effective in eradicating Legionella pneumophila from different watersamples. Both UV light and heat (60ºC) produced a 5 log kill in less than 1 h. Incontrast, both chlorine and ozone required 5 h of exposure to produce a 5 logdecrease. Neither turbidity nor the higher temperature of 43ºC impaired the efficacyof any of the disinfectant methods.